The Movement of Postcolonialism by Kiai Sholeh Darat Against the Dutch Colonialism (Study of Social-Religious Decolonization in Java 19th and 20th Century) - Maulana, Luthfi; Hak, Nurul; Abdurahman, Dudung (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2023)
This study discusses the postcolonial movement of Kyai Sholeh Darat in fighting against Dutch colonialism at the end of the 19-20 centuries. This study is interesting because so far there has been a physical resistance movement against colonial figures. This study finds Kyai Sholeh's postcolonial movement through his cultural approach. Methodologically, this research is included in the library research category to produce historical research studies based on postcolonial movements carried out by Kiai Sholeh Darat. From this it was found that the movement culture of Kiai Sholeh Darat in post-Java War 19th and early 20th century Java was seen as a postcolonial spirit and identity, with evidence showing a tendency towards a series of domination colonial regimes in various lines of life of the Javanese people. Cultural movement made by Kiai Sholeh Darat reflects the identity of the postcolonial movement through movement literacy manifested into publishing writings in the pegon script and translating the Qur’an into Javanese as a form of resistance against the colonial project seeking to separate Java from Islam. Kyai Sholeh also carried out kyai regeneration as a form of forming religious cadres and nationalist and conducts education for the Javanese people with da’wah from village or city in Java. This research contributes to the development of research related to the Kiai Sholeh Darat’s movement in preparing militant and religious cadres.